Narratives of disability and illness in the fiction of J. M. Coetzee - Wojtas, Paweł (Edinburgh University Press, 2024)
A comprehensive study of the representations of disability and illness in the fiction of J. M. CoetzeeStudies both Coetzee’s published novels and selected unpublished draftsExplores literary depictions of sensory, physical and intellectual disabilityDiscusses disability issues from the interdisciplinary perspective of literary and cultural theory and philosophyRereads Coetzee’s novels from the perspective of Disability StudiesResponds to the latest debates and issues in Disability Studies, such as disability and illness metaphors, neoliberal ableism and inclusionism, forms of sensory normativism: ocularcentrism and phonocentrism, disability biopolitics, intersectional disability, links between disability and ecocriticism, dependency and care, bibliotherapyThis study offers a detailed analysis of the fiction of J. M. Coetzee, including the novels of the South African and Australian periods, to demonstrate the development of Coetzee’s engagement with the complexities of non-normative embodiment. In this illuminating monograph, Paweł Wojtas demonstrates the extent to which Coetzee’s multifaceted depictions of disability offer a sustained critique of the ableist implications of political violence and neoliberal inclusionism alike. Exploring a wide range of notions, such as ocularnormativism, mute speech, eco-disability, disability Gothic, dismodernism, autogerontography, and bibliotherapy, Wojtas shows how Coetzee’s ‘disabled textuality’ provokes a sustained meditation on various forms of cultural denigration of disability experience